Cytotoxic Activity of Ethanol Extract of Piper aduncum L. on T47D Breast Cancer Cell Line using the MTT Method - Bellatasie, Rezlie; Oktavia, Sri; Rakhmil, Hanaya Fathiha; Uyun, Hendri Satria Kamal (Majalah Obat Tradisional, 2024)
Cancer treatment is known to cause side effects ranging from mild to severe, which can also affect the quality of the patient's health. Natural ingredients are an alternative source of cytotoxic substances with good anticancer activity and minimum side effects. Sirih hutan (Piper aduncum L.), also known as spiked pepper, is a medicinal plant with potential cytotoxic activity. This study aims to determine the cytotoxic activity of the ethanol extract of P. aduncum L. leaves with the Microculture Tetrazolium Test method. Phytochemical screening showed that P. aduncum L. contains alkaloids, flavonoids, saponin, phenol, and steroid/terpenoid compounds. The cytotoxic activity test was carried out on T47D cells with a concentration of 100 µg/mL, 10 µg/mL, 1 µg/mL, and 0.1 µg/mL test solution. The obtained IC50 value of the ethanol extract of P. aduncum L. was 171.2 µg/mL, belonging to the moderate toxic category. From this study, it is concluded that P. aduncum L holds potential as an anticancer agent.